Dubbelzinnigheid als historische deugd. Een antwoord aan Knegtmans, Zondergeld en Caljé - Berkel, Klaas van (BMGN - Low Countries Historical Review, 2006)
Klaas van Berkel, Ambiguity as an historical virtue. A response to Knegtmans, Zondergeld and CaljéAcademic illusions is indeed a rather ambiguous book, but that does not excuse a reviewer from the obligation to cite it correctly. Had Knegtmans in fact done this, he would have acknowledged that the University of Groningen, where the ideals of the academic community were adhered to so strongly, was indeed representative of the common academic pattern in the Netherlands, whereas the denominational universities deviated from this pattern only temporarily. In the case of Zondergeld, the habit of misreading crucial sentences seems to indicate an unwillingness to acknowledge that there are more ways of looking at so-called facts and people’s behaviour than just one. Caljé on the other hand does indeed recognize the ambiguity of the past, but fails to appreciate the essential ambiguity of the university. He is correct in stressing the political element in the history of the university, but forgets that the university also professes to be functionally detached from society. This repsonse is part of the discussion forum 'Academische illusies' (K. van Berkel).